Investigation of fine structure formation of guide field reconnection during merging plasma startup of spherical tokamak in TS-3U. (4th July 2019) - Tanabe, H.; Cao, Q.; Tanaka, H.; Ahmadi, T.; Akimitsu, M.; Sawada, A.; Inomoto, M.; Ono, Y.
Abstract: Ion heating/transport and its fine structure formation process through magnetic reconnection have been investigated by high guide field tokamak merging experiments in TS-3 and TS-3U. In addition to the previously reported demonstration of high-temperature plasma startup without center solenoid, the detailed fine structure formation process of reconnection heating has been revealed using new 96CH/320CH ultra-high-resolution 2D ion Doppler tomography diagnostics. By identifying the double-axis field configuration with the X -point on the midplane using in situ magnetic probe diagnostics, the detailed measurement successfully revealed that the ion temperature profile forms two types of characteristic heating structure, both around the X -point and downstream. The former is affected by the Hall effect to form a tilted heating profile, while the latter is affected by the transport process which a forms a poloidal double-ring-like structure. The achieved ion heating mostly depends on the reconnecting component of the magnetic field, and the contribution of the guide field to decrease the heating efficiency tends to be saturated in the high guide field regime. Under the influence of better toroidal confinement with higher guide field, the downstream ion heating is transported vertically, mostly by parallel heat conduction, and finally forms a poloidal ring-like hollow distribution aligned with the closed flux surface at the end of merging.